EFL TEACHERS’ TRANSFORMATION: BURNOUT AND RESILIENCE EXPERIENCES IN TEACHERS’ PROFESSIONAL IDENTITY CONSTRUCTION THROUGH CRITICAL INCIDENT TECHNIQUES - Anselma, Yonas Yona; Mbato, Concilianus Laos (Language Circle: Journal of Language and Literature, 2023)
Even though previous researchers recognized professional identity change as one of the most vulnerable stages for EFL teachers, only a few researched it in Indonesia's context, applying the critical incident technique. Thus, this study aimed to investigate the EFL teachers’ professional identity transformation through teachers’ factors and how those factors influence their professional identity. This study used the Critical Incidents Technique (CIT) to employ an open-ended questionnaire for Focus Group Discussion (FGD) and Individual in-depth interview to gather the data. Five teachers from different schools in Sintang, West Kalimantan, were purposively chosen as the study participants. The results showed that the teacher faced three personal, interpersonal, and organizational stress factors. The personal factors were related to teachers’ emotional control and self-efficacy. Interpersonal factors were related to students’ behavior in the classroom and negative relationships with colleagues. Meanwhile, organizational factors were related to the lack of media facilities and salary. Despite the stress, EFL teachers showed their ability to cope. The participants broadened on how they dealt with the situation, how stressors affected their identity as teachers, such as preserving their motivation to become teachers, and how they overcame job dissatisfaction.